PENGENDALIAN HAMA THRIPS(Thysanoptera : Thripidae) DENGAN MENGGUNAKAN EKSTRAKDAUN KENIKIR (Cosmos caudatus) PADA TANAMAN CABAI MERAH: Pest Thrips Control (Thysanoptera: Thripidae) by using KenikirLeaf Extract (Cosmos caudatus) on Red Chili Plants - Muhammad Izzdin Idrus; Haerul Haerul; Erni Nassa (Jurnal Agrotan, 2018)
This study aims to determine the effectiveness of Kenikir leaf extract in reducing thrips pest populations in red chili plants. This research was conducted in November 2017 to February 2018 in Sege-Segeri, Minasabaji, Bantimurung District, Maros Regency. This study used a Randomized Block Design (RBD) consisting of 4 doses of kenikir leaf extract treatment namely ; K0 (without kenikir leaf extract), K1 (giving kenikir leaf extract with a dose of 20 ml / liter of water), K2 (giving kenikir leaf extract with a dose of 40 ml / liter of water), and K3 (giving Kenikir leaf extract with a dose of 60 ml / liter of water). Each treatment was repeated three times so there were 12 experimental units. The results showed that kenikir leaf extract effectively reduced and controlled the population of Thrips pests in red chili plants where the best dose was 60 ml / liter of water